An Investigation of the cultural intelligence of pre-service music teachers in Turkish Universities - Celik, Sibel (Rastros Rostros, 2023)
Culture constitutes all the values of a society; they are all the building blocks that can be transferred, renewed, and come from the past to the present. Turkey is a diverse, rich and culturally diverse country. In today's world, the concept of cultural intelligence, which is necessary for people to adapt in different and multicultural environments is substantial. In this context, it is extremely important for music teachers to adapt in multicultural environments for their efficient work. This purpose of this study is to investigate of pre-service music teachers’ cultural intelligence and to determine by some variables whether differ or not.  This study was conducted with quantitative research methods. Descriptive analysis, Independent Group t-test, One-Way Analysis of Variance (ANOVA), Kruskal Wallis-H Test, Pearson Correlation Coefficient were used. In study, which was carried out with quantitative research, 278 participants who study at seven various regions of Turkey in the 2020-2021 academic year. It has been determined that the cultural intelligence levels are at a good level and the relations between them are positive. Cultural intelligence levels of participants do not differ significantly by the gender, age, university, parents' education status. Solely it was found statistically significant whether there was someone involved in music in the family in metacognition and cognition sub-dimensions. As a result, it was seen that the cultural intelligence levels of the pre-service music teachers were good and generally did not differ according to demographic variables. The novelty of this  study  is  that  the  framework  has  identified preservice music teachers’ cultural intelligence levels in Turkey.  Furthermore, this study can  be  a  point  of  reference  to  stakeholders and researchers on this music education axis.  The findings of this study also serve to foresee education sector about the issues related to the implementations of higher institutions of teacher educations.
Keywords: pre-service music teachers; music education; multiculturalism; teacher education; cultural intelligence